Features of Service Members' Adaptation to Civilian Life: Legal Aspects - Bontlab, Vasyl (2022)
The purpose of the study is to analyze the regulatory and legal support for the adaptation of service members to civilian life in the United States, France, and Germany to identify elements that could be useful for implementation in Ukrainian legislation. The 5 stages of adaptation that each service member goes through after completing his/her service when returning to civilian life are identified and analyzed. It is found that all analyzed countries begin the adaptation process several months (or years) before the end of service. In addition, former service members consistently receive financial assistance. The obtained results can be used by scientists for further analysis of regulatory and legal support and, on its basis, direct implementation of procedures for adaptation of service members to civilian life